Numerical Investigation of Intra-abdominal Pressure Effects on Spinal Loads and Load-Sharing in Forward Flexion - Liu, Tao; Khalaf, Kinda; Adeeb, Samer; El-Rich, Marwan (Frontiers in Bioengineering and Biotechnology, 2019)
The intra-abdominal pressure (IAP), which generates extensor torque and unloads the spine, is often neglected in most of the numerical studies that use musculoskeletal (MSK) or finite element (FE) spine models. Hence, the spinal loads predicted by these models may not be realistic. In this work, we quantified the effects of IAP variation in forward flexion on spinal loads and load-sharing using a novel computational tool that combines a MSK model of the trunk with a FE model of the ligamentous lumbosacral spine. The MSK model predicted the trunk muscle and reaction forces at the T12-L1 junction, with or without the IAP, which served as input in the FE model to investigate the effects of IAP on spinal loads and load-sharing. The findings confirm the unloading role of the IAP, especially at large flexion angles. Inclusion of the IAP reduced global muscle forces and disc loads, as well as the intradiscal pressure (IDP). The reduction in disc loads was compensated for by an increase in ligament forces. The IDP, as well as the strain of the annular fibers were more sensitive to the IAP at the upper levels of the spine. Including the IAP also increased the ligaments’ load-sharing which reduced the role of the disc in resisting internal forces. These results are valuable for more accurate spinal computational studies, particularly towards clinical applications as well as the design of disc implants.